Obstetrics Practice Manual for Primary Health Care - Enio Pablo Castiñeira González; Roberto Pérez García; Iris María Ferreiro González; Juan Carlos Pastrana Tapia; José Luis Gómez Miranda; Alejandro Argíz Muñiz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
In order to reduce errors in the process of care for both women in childbearing age and pregnant women, professional's training needs to be permanent. Therefore, this Manual, though far from pretending to be a finished Obstetrics book, aims to provide an essential working tool for family doctors, who are in the front line of confrontation with the health of women in general and more specifically with pregnant women in Cienfuegos. It is based on the latest version of the Obstetrics Consensus, circulating this year, and includes also a review on the statements of several specialists colleagues who work in different profiles in the province